Berinvestasi di Era Digital: Peluang dan Tantangan bagi Ibu Rumah Tangga - Fitri, Nuri Annisa; Yulistarini, Dian; Even, Nur; Yuliawati, Sari (PUBLIKASI PENGABDIAN KEPADA MASYARAKAT, 2025)
The theme of the Counseling in this Community Service (PkM) activity is "Investing in the Digital Era: Opportunities and Challenges for Housewives". This activity aims to invite participants to realize the importance of investment and start investing in the Capital Market. In addition, through this activity, it can straighten out the negative stigma that says that only entrepreneurs or those with large funds can become investors. This PkM was held at the South Sumatra Provincial Transportation Office on August 20, 2024. The Counseling method was used in this PkM activity. The results of the PkM activity, participants became increasingly aware of the importance of investing in the Capital Market to ensure safe finances for the future. Participants are very aware that inflation can affect economic stability. Therefore, it is important to start investing to be ready to face inflation and other challenges that can disrupt a person's financial stability. Furthermore, through this activity, it has broken the negative stigma that says that only entrepreneurs or those with large funds can become investors. Anyone can start investing, even with a small amount of money. Securities Company through Unanti provides facilities for participants who want to start investing by opening a securities account.